Control interno en las empresas públicas de servicios que operan en las instituciones del Estado - Campelo Castro, Diana Karen (2022)
The research project analyzes internal control in public service companies that operate in higher education institutions, determining if compliance with internal control influences financial statements, its purpose is to verify the procedures of operational management that will minimize risks. The Technical Report was developed where the facts found in the interviews and documentary analysis were exposed; In the results obtained, the components of internal control were evaluated, where the important risks that arose were determined..........